Masalah-Masalah yang Dihadapi Siswa yang Berasal dari Keluarga Broken Home dan Implikasinya terhadap Program Layanan Bimbingan dan Konseling - Rahmi, Sharfina; Mudjiran, Mudjiran; Nurfahanah, Nurfahanah (Konselor, 2014)
Abstract, broken home’s family is the family that function of father and mother do not work functionally. Child that experience this situation called broken home child. This research aim’s to look at the description of the problems that face by student who wellborn in broken home’s family in SMA N 1 Banuhampu. This research is descriptive research, that see problems which are faced by student who wellborn in broken home’s family. The subject of this research is 39 students. Research instrument is questionnaire. The results of this research is the student have a problems in academic, themselves, family lives and peer relations. In this situation guidance and counseling teacher could arrange guidance and counseling service program that match with problems of students who from broken home’s family.